IMPLEMENTASI AREA WAJIB KONDOM TERHADAP WANITA PEKERJA SEKSUAL DI RESOSIALISASI ARGOREJO KOTA SEMARANG - Fairuza Alief; Zahroh Shaluhiyah; Priyadi Nugraha Prabamurti (Jurnal Kesehatan Masyarakat (Undip), 2017)
In 2013, Semarang City was ranked first with the highest HIV cases in Central Java. Therefore, Resosialisasi Argorejo as a red-light district implemented 100% mandatory condom usage since 2008. The purpose of this study is to describe and analyze in detail the implementation of mandatory condom usage system in Resosialisasi Argorejo from the aspects of input, process and output. This type of research is quantitative qualitative research with in-depth interview to the officers and interview with questionnaire to sexual workers. The population is 22 key informants consist of 9 Resosialisasi officers, 1 Peer Educator, 3 Pokja Lokasi, 6 health workers, 3 pimps and six informants triangulation consisting of the Chairman of  Resosialisasi Argorejo, Officer of Kalibanteng Kulon Region, Head of Puskesmas Lebdosari, and each pimp’s sexual workers. For quantitative, 90 respondents are selected using cluster sampling technique. Research showed that condom usage is 64.4%, the good implementation of Mandatory Condom Usage is 63.3%, 56.7% got a good support from peer educator, 63.3% got a good support from health officer, 51.1% got a good support from pimps, 71.1% have a good access to Mandatory Condom Usage information-related and 63,3% have a good availability of condoms. Viewed from the aspect of the process, planning is done unsystematically and poorly and unclear job description for the implementation itself. Supervision has been done for sexual workers and pimps, but no supervision has been applied to Condom Mandatory Area officers. Monitoring has been done but has not been done routinely. Evaluation has been done but there has been no systematic follow-up. In terms of input, the number of human resources is still inadequate and there are still those who have not received training to work in Resosialisasi Argorejo. Self-funding impedes good implementation, especially on STI and VCT screening tests Moreover, there is no written SOP applicable in Resosialisasi Argorejo. The distribution of condoms is well done, but no strict sanctions have been imposed for customers who do not use condoms. The proposed recommendation is to increase the number of human resources according with suitable competence, compulsory training to become officers, the need for written SOP, the need for strict sanctions and have to be implemented, strengthen the relationship between the relevant instancies, as well as a re-evaluation of BLUD implementation